Advancing national greenhouse gas inventories for agriculture in developing countries: Improving activity data, emission factors and software technology - Ogle, Stephen Michael; Buendia, L.; Butterbach-Bahl, Klaus; Breidt, F.J.; Hartman, M.; Yagi, K.; Nayamuth, R.; Spencer, S.; Wirth, T.; Smith, Pete (IOP Publishing, 2013)
Developing countries face many challenges when constructing national inventories of greenhouse gas (GHG) emissions, such as lack of activity data, insufficient measurements for deriving country-specific emission factors, and a limited basis for assessing GHG mitigation options. Emissions from agricultural production are often significant sources in developing countries, particularly soil nitrous oxide, and livestock enteric and manure methane, in addition to wetland rice methane. Consequently, estimating GHG emissions from agriculture is an important part of constructing developing country inventories. While the challenges may seem insurmountable, there are ways forward such as: (a) efficiently using resources to compile activity data by combining censuses and surveys; (b) using a tiered approach to measure emissions at appropriately selected sites, coupled with modeling to derive country-specific emission factors; and (c) using advanced software systems to guide compilers through the inventory process. With a concerted effort by compilers and assistance through capacity-building efforts, developing country compilers could produce transparent, accurate, complete, consistent and comparable inventories, as recommended by the IPCC (Intergovernmental Panel on Climate Change). In turn, the resulting inventories would provide the foundation for robust GHG mitigation analyses and allow for the development of nationally appropriate mitigation actions and low emission development strategies.